HERZBERG’S THEORY AND JOB SATISFACTION OF SCHOOL NURSES IN BAHRAIN - Hasani, Faten Ali (LIFE: International Journal of Health and Life-Sciences, 2020)
School nurses are a vital part of the academic life and success of students in the schools, as they satisfy all students’ health needs and provide them with optimal healthcare so that they can undertake their academic tasks. In order to better understand these roles, this study aimed to investigate the factors affecting job satisfaction of school nurses in Bahrain within the views of Herzberg’s two-factor theory by explaining how certain factors of a job provide job satisfaction, while other factors provide job dissatisfaction. This study used a mixed-method approach: a total of 142 school nurses in Bahrain were surveyed and data were collected using the Measure for Job Satisfaction (MJS) (Traynor & Wade, 1993) to measure job satisfaction. Twenty-seven school nurses were subsequently recruited for interviews using a purposeful sampling procedure. The data were subjected to thematic analysis using Burnard’s (1991) framework. Results from the surveys were indicative of a generally high level of job satisfaction among school nurses in Bahrain. The areas which contributed most strongly to this satisfaction, by way of statistical significance, were perceptions of the standard of care provided, professional support that the nurses received, the manageability of assigned workloads and personal satisfaction.